Marketing aspect of corporate social responsibility - Leković Ksenija; Đokić Ines (Anali Ekonomskog fakulteta u Subotici, 2014)
Nowdays, in extremely complicated world, every business is faced with numerous number of innovations, incertitudes and opportunities. The best ideas are those which make companies big, while on the other hand, customers, and not capital, are increasingly becoming the most precious resource of business. Holistic marketing concept is a marketing approach that tries to accept and reconcile the scope and complexity of the new age marketing activities, including socially responsible marketing and, also, calls marketers to consider the social and ethical aspects of their marketing practices. Due to the fact on which the social responsibility of the company is currently one of the most dynamic modern business concepts, the aim of this paper is reflected in the efforts to highlight the importance of corporate social responsibility and socially responsible marketing as contemporary trends and ways how companies survive in the highly variable and competitive environment. From the main aim of this paper stems the derived aim that seeks to point out the position of socially responsible behavior in Serbia and its further development, considering the conditions in which the Serbian economy is in recent decades.